Parenting Styles Among Adolescents: A Comparative Study of Nuclear and Joint Families (Indian Journal of Psychology & Education, 2014)
Adolescence is described as the stage of stress and storm. It is the beginning of the puberty with rapid spurt in physical, cognitive- psychological and social characteristics. The pivotal role that parents play in a child’s development is undisputed. The differences in parenting practices have profound and lasting effects on all aspects of development. Family structure also plays a very important role on the adolescents. So, present study was designed to examine the parenting styles among adolescents of Nuclear and Joint families. The objectives of the study were (i) to study the parenting styles among adolescents from nuclear and joint families (ii) to study the parenting style among male and female adolescents (iii) to study the interactional effect of family structures and gender on parenting styles. For this purpose Parental Authoritative Questionnaire by Buri (1991) was used. The sample consisted of 120 adolescents where equal number subjects were from nuclear and joint families. Moreover the gender was also equally taken from both nuclear and joint families. The data was analyzed with the help of ANOVA and t-test. Significant differences between the comparison groups were observed on the parenting styles. The results have been discussed in the light of operational definition of the variables.